倫理學的辯護和支持: 放棄治療: Withdrawing Treatment: Ethics Defense and Support - DU, Zhizheng (International Journal of Chinese & Comparative Philosophy of Medicine, 2000)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 儘管醫學在飛速進步，但由於種種原因，放棄治療在臨床中有日益增多的趨勢。放棄治療是人們的一種理性選擇。合理的放棄治療是醫學人道主義在某種特殊情況下的理性表現。區分放棄治療的不同情況，正確界定放棄治療的範圍，合理選擇放棄治療的措施，確保不發生不應放棄治療的病人被放棄，在全過程中始終尊重病人的自主權，妥善處理對於是否放棄中的分岐，並維護病人的整體利益，是履行放棄治療中倫理學應予充分注意的問題。 Many believe that giving up treatment always conflicts with physicians' duty and responsibility. However, although societies have achieved the rapid advancing of medical sciences and technologies, and although patients and families sometimes want to maintain life-sustaining interventions at any cost, renunciation of futile treatment remains an unavoidable issue facing physicians in their clinical practice. This is especially the case for Chinese society today. This paper argues that withdrawing life-sustaining therapy is not always opposite to moral requirement. Specifically, the paper explores the following important issues around the decision making of renouncing treatment. First, in what medical situation does the patient and the family's request for withdrawing treatment should be granted by the physician? this paper contents that a necessary condition must be that the patient suffers an incurable disease. Second, who has the right to make the decision of renouncing treatment? This paper argues that, in considerations of Chinese ethical and societal character, some practical measures should be establishes in Chinese society medical and moral consideration should all be balanced and integrated. Finally, in order to avoid unnecessary ambiguities and disputes, this paper suggests that legal and administrative procedures and guidelines should be adopted regarding the decision of renouncing treatment. DOWNLOAD HISTORY | This article has been downloaded 31 times in Digital Commons before migrating into this platform.